Antimicrobial, Nutritional And Phytochemicakal Properties Of Perinati Excelsa Seeds - STEPHEN A. ENABULELE; JOSEPH E. EHIAGBONARE (International Journal of Pharma and Bio Sciences, 2011)
Seeds of Perinari excelsa were investigated for its antimicrobial, nutritional and phytochemical properties. Results of the study show that the aqueous and ethanolic extracts of the seed were active against both gram negative and gram positive organisms used. Important bioactive constituents present in the extracts were alkaloids, anthraquinones, cardiac glycosides, flavonoids, saponins, phenolic compounds and tannins. Yield extracts of the powdered seeds, was 8.45% for water and 6.32% for ethanol indicating that water was the better of the two solvents used. Results of the antibacterial activity of the extracts reveal that the ethanolic extracts at different concentrations were more active against the test organisms namely Staphylococcus aureus, Klebsiella pneumonia, Escherichia coli and Salmonella typhi than the aqueous extracts. The MIC values for the aqueous extract ranged between 13.0 and 14.0 mg/ml while that of ethanolic extract was between 12.5 and 14.0 mg/ml. The MBC values for aqueous extract ranged between 14.0 and 15.5 mg/ml while that of ethanolic extract ranged between 13.0 and 15.0 mg/ml. Nutritionally, result from the study justifies the use of the seed both as spice and food component by locals. The seed was particularly found to be very rich in iron. Therefore there is a need for further studies on the plant seed in order to isolate, identify and characterize the active components to maximize the potential of this useful seed.